Organizational Culture, Motivation, and Climate Determine Employee Performance at PT ROMI: Budaya Organisasi, Motivasi, dan Iklim Kerja Mempengaruhi Kinerja Karyawan di PT ROMI - Putra, Dea Septa Fradana; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2025)
General Background Human resources (HR) represent a crucial asset for company success, requiring careful management to ensure optimal contribution. Specific Background Despite the general importance of HR, employee performance at PT ROMI Sidoarjo has exhibited a declining trend from 2021 to 2023 , marked by on-the-job issues such as unpunctuality and low work quality. Knowledge Gap Existing academic literature presents conflicting evidence regarding the specific influence of organizational culture, work motivation, and organizational climate on employee performance. Aims This study aims to analyze the role of organizational culture, work motivation, and organizational climate in determining employee performance at PT ROMI Sidoarjo. Results Utilizing a quantitative method with a sample of 125 employees selected via purposive sampling , the findings indicate that organizational culture, work motivation, and organizational climate all have a positive and significant effect on employee performance. Novelty This research contributes by confirming the strong, synergistic role of these three internal factors within the specific context of performance challenges at PT ROMI Sidoarjo. Implications Management should focus on consistently reinforcing the organizational culture, providing targeted motivation, and maintaining a positive organizational climate to reverse the declining performance trend. Highlights: Organizational culture positively correlates with employee performance in the manufacturing sector. Work motivation and organizational climate are confirmed as positive predictors of performance. The combined effect of three variables helps stabilize performance amidst a challenging corporate environment. Keywords: Organizational Culture, Work Motivation, Organizational Climate, Employee Performance, PT ROMI